Apa yang Mahasiswa Pikirkan tentang Statistika? - Hikmah Ramdhani Putri; Prayogi Dwina Angga (Departement of Mathematics Education, 2024)
This study aims to describe the views of PGSD students of Mataram University regarding statistics and its teaching. This type of research is a survey given to 142 PGSD students who have taken educational statistics courses as a sample. The research instrument is a questionnaire distributed via Google Forms. The data analysis used is descriptive statistics with the help of SPSS software. The study results are divided into two aspects: views on statistics and teaching statistics. The results obtained from the aspect of views on statistics are (1) The understanding of statistics as the development of science and a branch of statistical science is an understanding that has been agreed upon by most students; (2) Regarding the objectives of the statistics course at the University of Mataram which is mandatory, students stated that they agree that the objective is to draw valid conclusions in research. Furthermore, the results obtained in terms of views on statistics teaching are: (1) Most students have the main motivation to study statistics to fulfill semester credit units and want to master and apply the main lecture material; (2) The hope of most respondents after taking the statistics course is to be able to apply statistics in research/final assignments; (3) if they have difficulty understanding the material, students will ask their colleagues.